2011
DOI: 10.1088/1742-6596/320/1/012079
|View full text |Cite
|
Sign up to set email alerts
|

Low temperature magnetism of the metallic pyrochlore oxide Pr2+xIr2−xO7+δ

Abstract: Abstract. Pr 2 Ir 2 O 7 is a metallic pyrochlore compound which has been revealed to form a spin liquid phase by recent studies. Here we report results of magnetic and electrical transport properties of a newly synthesized polycrystalline sample of Pr 2+x Ir 2x O 7+ with excess Pr. A clear anomaly in the temperature dependence of the electrical resistivity is observed at 0.8 K, suggesting a phase transition into some sort of ordered state. IntroductionIt has been widely recognized that geometrical frustratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…For x = 0.95, a slight drop in electrical resistivity is observed at T O = 0.67 K. Interestingly, for x = 0.90, two anomalies are observed at 1.3 and 0.5 K. Next, we will discuss these transitions at x = 0.90 Figure 3 shows the reciprocal magnetic susceptibilities of (Nd 0.10 Pr 0.90 ) 2 Ir 2 O 7 in a magnetic field of 1 kOe. The effective magnetic moment of (Nd 0.10 Pr 0.90 ) 2 Ir 2 O 7 is estimated to be 2.55 µ B by Curie-Weiss fitting for data below 14 K. This value is in good agreement with 2.73 µ B for Ln = Nd and 2.68 µ B for Ln = Pr [16,19]. This results in the similar characteristics of the CEF ground state in both compounds.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…For x = 0.95, a slight drop in electrical resistivity is observed at T O = 0.67 K. Interestingly, for x = 0.90, two anomalies are observed at 1.3 and 0.5 K. Next, we will discuss these transitions at x = 0.90 Figure 3 shows the reciprocal magnetic susceptibilities of (Nd 0.10 Pr 0.90 ) 2 Ir 2 O 7 in a magnetic field of 1 kOe. The effective magnetic moment of (Nd 0.10 Pr 0.90 ) 2 Ir 2 O 7 is estimated to be 2.55 µ B by Curie-Weiss fitting for data below 14 K. This value is in good agreement with 2.73 µ B for Ln = Nd and 2.68 µ B for Ln = Pr [16,19]. This results in the similar characteristics of the CEF ground state in both compounds.…”
Section: Resultssupporting
confidence: 64%
“…For x = 1, a slight drop in electrical resistivity is observed at T O = 0.8 K, suggesting a long ranged order (LRO). It is reported that a polycrystalline sample of Pr 2 Ir 2 O 7 shows an anomaly at 0.8 K although the single crystalline sample shows spin liquid behavior without LRO [18,19]. However, the origin of anomaly at 0.8 K is not still clearly understood.…”
Section: Resultsmentioning
confidence: 99%
“…It is known that frustrated magnets often exhibit strong sample dependence due to the frustration among spin interactions and many-body effects. This tendency has also been found in pyrochlore oxides A 2 B 2 O 7 (A = rare earth ions, B = transition metal ions) [8][9][10][11]44,[47][48][49][50] , including NIO 8,10 and EIO 8,10,11 , as well as PIO 8,10,44 , where the distribution of nonstoichiometric concentrations such as x and y of A 2+x B 2−x O 7+y is thought to induce sample dependent physical properties 11,44,[47][48][49][50] . Even in our samples, we also observed a slight discrepancy in EIO for the previous results.…”
Section: Discussionmentioning
confidence: 73%
“…The prepared samples exhibit qualitatively the same behaviors of M/H, C P , and ρ as those of the previous reports (Figs. 2 and 3) [9][10][11]44,46 . We confirmed that the second-order phase transition of the MIT appear at T MIT = 34 K for NIO and at T MIT = 120 K for EIO (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation